Philosophical Foundations And Ontological Dimensions Of Social Responsibility - Abdullayeva Iroda (Zien Journals, 2025)
This article examines the conceptual essence of social responsibility as a fundamental category in social and philosophical sciences. It emphasizes that for the successful realization of existing programs and projects within the social sector, the participants must possess a heightened sense of individual and collective responsibility. Social responsibility, as a socio-philosophical concept, reflects the essential principles governing the interaction between the individual and society in all dimensions of life. It plays a pivotal role in maintaining social stability, fostering moral awareness, and supporting the sustainable development of communities
Keywords: responsibility; social responsibility; historical approach; methodological approach